2018
DOI: 10.1016/j.bjan.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Bloqueio do plano abdominal transverso guiado por ultrassom em pacientes submetidos à colecistectomia laparoscópica: comparação da eficácia de bupivacaína e levobupivacaína no controle da dor pós‐operatória

Abstract: Bupivacaine and levobupivacaine showed similar efficacy at TAP block in patients undergoing laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Many studies on laparoscopic TAP block used bupivacaine as a local anaesthetic. [17] But we have used ropivacaine because it is safer and is equally effective. [1819] Studies have demonstrated pain relief, lesser narcotic use and shorter hospital stay with the use of laparoscopic-guided TAP.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on laparoscopic TAP block used bupivacaine as a local anaesthetic. [17] But we have used ropivacaine because it is safer and is equally effective. [1819] Studies have demonstrated pain relief, lesser narcotic use and shorter hospital stay with the use of laparoscopic-guided TAP.…”
Section: Discussionmentioning
confidence: 99%